Hierarchical mesoporous bio-polymer/silica composites co-templated by trimethyl chitosan and a surfactant for controlled drug delivery - Rana, Vijay Kumar; Park, Sung Soo; Parambadath, Surendran; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Medchemcomm, 2011)
In this communication, we report the facile synthesis of hierarchical mesoporous bio-polymer/silica composite materials with bimodal mesopores using a dual-template of the cationic N,N,N-trimethyl chitosan (TMCs) and the anionic sodium dodecyl sulfate (SDS) via one-step synthetic strategy. Tetraethoxysilane (TEOS) was used as a silica source. The nitrogen adsorption/desorption measurements and transmission electron microscopy analysis showed the hierarchical structure of the mesoporous bio-polymer/silica composites with bimodal mesopores having an average pore size of 5-7 nm with the visible voids between the silica nanoparticles, which allow the mesoporous bio-polymer/silica composites to encapsulate a large number of guest drug molecules, Ibuprofen (IBU) or 5-fluorouracil (5-FU), due to their high surface area and pore volume. In addition, the mesoporous chitosan-silica composites also had a long term biocompatibility for the target release of the drug molecules to the CEM cells, MCF cells, etc. as well as a pH sensitive controlled release behavior of the drug molecules.

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Heterocyclic tri-urea isocyanurate bridged groups modified periodic mesoporous organosilica synthesized for Fe(III) adsorption - Rana, Vijay Kumar; Selvaraj, M.; Parambadath, Surendran; Chu, Sang-Wook; Park, Sung Soo; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Solid State Chemistry, 2012)
To achieve a high level of heavy metal adsorption, 1,1',1 `'-(1,3,5-triazine-2,4,6-triyl)tris(3-(3-(triethoxysilyl) propyl)urea) (TTPU) was synthesized as a novel melamine precursor and incorporated on the silica surface of periodic mesoporous organosilica (PMO). The melamine modified PMOs (MPMOs) were synthesized under acidic conditions using TTPU, tetraethylorthosilicate (TEOS) and Pluronic P123 as a template and the modified PMOs were characterized using the relevant instrumental techniques. The characteristic materials were used as adsorbents for the adsorption of Fe(III) ions. Fe(III) adsorption studies revealed MPMO-7.5 to be a good absorbent with higher adsorption efficiency than other MPMOs. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Adsorption efficiency; Fe(III) adsorption; Melamine; Periodic mesoporous organosilica (PMO)

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing